Ratiometric fluorescent detection of Hg(II) by amino-acid based fluorescent chemodosimeter using irreversible reaction of phenylboronic acid with mercury species. (July 2021) - Subedi, Sumita; Neupane, Lok Nath; Mehta, Pramod Kumar; Lee, Keun-Hyeung
Abstract: Boronic acids have been widely employed as important intermediates for various organic syntheses and reversible receptors for glucose and carbohydrates. We developed a new ratiometric fluorescent chemodosimeter for Hg 2+ based on an irreversible reaction of phenylboronic acid with Hg 2+ . The fluorescent chemodosimeter (1 ) bearing a phenylboronic acid as a reaction site showed a selective and sensitive ratiometric signal behavior to low concentrations of Hg 2+ ions in aqueous solutions containing 1% CH3 CN. The ratiometric signaling was not considerably inhibited by coexisting other metal ions. The detection limit was measured to be 7.0 nM for Hg 2+ based on the linear ratiometric signal to the nanomolar concentration (0–500 nM) of mercury ions. The signal mechanism study revealed that 1 reacted with Hg 2+, providing covalent product of mercury ion (3 ) by replacement reaction of the boronic group of 1 with Hg 2+, which exhibited fluorescent spectrum changes. The reaction kinetic study suggested that the rate law of the reaction is 1st order in Hg 2+ and 1st order in the probe, and 2nd order overall. Real world application of the fluorescent chemodosimeter was demonstrated by quantification of Hg 2+ ions in groundwater and tap water samples spiked with known amounts of Hg 2+ ions. Highlights: A ratiometric fluorescent chemodosimeter was highly sensitive to Hg 2+ and 1 equiv of Hg 2+ was enough for the completeness of the ratiometric response. The selective ratiometric detection was not interfered by other metal ions. The detection limit was measured to be 7.0 nM for Hg 2+ in aqueous solutions.